Thirty-year trends of anxiety disorders among adolescents based on the 2019 Global Burden of Disease Study - Jing Guo; Fan Yang; Shan Zhang; Xiaohan Liu; Ning Huang (General Psychiatry)
Background Anxiety disorders are the most common psychiatric problems, affecting approximately 1 in 12 children and 1 in 4 adolescents. Understanding the incidence, burden and correlated risks of anxiety disorders among children and adolescents can help identify areas of success, stagnation and emerging threats, thereby facilitating effective improvement strategies.Aims To estimate the incidence and burden trends of anxiety disorders in children and adolescents from 1990 to 2019 in 204 countries and compare the incidence and disease burden in different countries. To examine the association between anxiety disorders and social indicators (healthcare access and quality of life).Methods Data were obtained from the Global Burden of Disease Study 2019. The age-standardised incidence rates (ASIRs) and disability-adjusted life years (DALYs) were reported to assess the burden of anxiety disorders, and the estimated annual percentage change was calculated to quantify the temporal trends. Pearson’s correlation was used to investigate country-level risk factors for incidence and DALYs.Results Globally, there were 932 million incident cases of anxiety disorders in children and adolescents, 739.29 per 100 000 ASIRs and 380.62 million DALYs in 2019. From 1990 to 2019, the estimated annual percentage change of incidence of anxiety disorders decreased by 2.2%. Significant variations were observed in the age-standardised burden rate and the changing trend of anxiety disorders among countries. Portugal reported the highest ASIR of anxiety disorders, while Mexico had the largest increase rate of ASIR. In 2019, Portugal reported the highest number of DALYs (1001.71 million), and India (212.09 million) reported the lowest number of DALYs. The burden of anxiety disorders was positively correlated with the average number of psychiatrists, psychologists and nurses in the mental health sector (per 100 000), and quality of life and the correlation coefficients were 0.58, 0.67, 0.43 and 0.53, respectively.Conclusions The incidence and global burden of anxiety disorders in adolescents have continued to decrease over the past 30 years. However, the incidence and disease burden in developed countries are still increasing steadily. Policymakers should design and implement mental health strategies for adolescents based on their specific developmental status, as well as the cultural and regional characteristics of each country.